Pendidikan Karakter dalam Dunia Pendidikan - Sukatin, Sukatin; Munawwaroh, Siti; Emilia, Emilia; Sulistyowati, Sulistyowati (Lembaga Yasin AlSys, 2023)
Character formation is needed not only at school but also at home, in the social environment. The current program no longer targets young people attending early childhood education, but also adults. It is very important to maintain the life of this nation. The competition imagined what would unfold in the following years. Of course it will be a burden for us and our parents at this time. Children have to compete with their peers from various countries around the world. Even those of us who are still working in the future feel the same way. To demand quality human resources in the next millennium, good character is definitely needed. However, character is the main goal of an individual.